Country Economic Memorandum for Sao Tome and Principe - Background Note 13 : What Do We Know about Gender in São Tomé and Príncipe - Kirkwood, Daniel (World Bank, Washington, DC, 2019)
The objective of this note is to provide a summary of gender-related statistics and research in São Tomé and Príncipe in the areas of human capital, economic empowerment, and gender-based violence (GBV). The data comes from surveys conducted by the national statistics office and from international databases, such as the Women, Business, and the Law database and the various databases that feed into the World Development Indicators. Whenever possible the note compares the gender situation in STP with peer countries. It also summarizes data and knowledge gaps on gender. STP has made strong progress on gender equality in human capital yet has been unable to translate this into the economic empowerment of women. While its performance on gender-related indicators of human capital are like other middle-income countries, STP’s performance on indicators related to women’s economic empowerment more closely resembles its low-income neighbors. This is partly explained by traditional gender norms, which restrict women’s income generating versus their domestic role and impede their personal safety.